2014
DOI: 10.1371/journal.pone.0103978
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Hemodynamic Resuscitation May Fail to Optimize Tissue Perfusion: An Observational Study on the Effects of Dobutamine, Enoximone, and Norepinephrine in Patients with Acute Myocardial Infarction Complicated by Cardiogenic Shock

Abstract: AimTo investigate the effects of inotropic agents on parameters of tissue perfusion in patients with cardiogenic shock.Methods and ResultsThirty patients with cardiogenic shock were included. Patients received dobutamine, enoximone, or norepinephrine. We performed hemodynamic measurements at baseline and after titration of the inotropic agent until cardiac index (CI) ≥2.5 L.min−1.m−2 or mixed-venous oxygen saturation (SvO2) ≥70% (dobutamine or enoximone), and mean arterial pressure (MAP) ≥70 mmHg (norepinephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
(49 reference statements)
1
24
0
Order By: Relevance
“…Studies of other types of shock and cardiovascular compromise have reported the loss of systemic and microcirculatory coherence, showing this finding to be a common occurrence. Examples in addition to sepsis include traumatic hemorrhagic shock (96), heart failure (26,27), and malaria (44). A main area of research concerns the inability of fluid therapy to resolve the disparity between macro-and microcirculation (e.g., 53).…”
Section: Microcirculatory Heterogeneity and The Loss Of Hemodynamic Cmentioning
confidence: 99%
“…Studies of other types of shock and cardiovascular compromise have reported the loss of systemic and microcirculatory coherence, showing this finding to be a common occurrence. Examples in addition to sepsis include traumatic hemorrhagic shock (96), heart failure (26,27), and malaria (44). A main area of research concerns the inability of fluid therapy to resolve the disparity between macro-and microcirculation (e.g., 53).…”
Section: Microcirculatory Heterogeneity and The Loss Of Hemodynamic Cmentioning
confidence: 99%
“…Inotropic agents are popular in current treatment guidelines for HF and dobutamine is recommended in parenteral therapy for inotropic support [15,16]. Dobutamine is a synthetic catecholamine widely used in the management of stress, cardiogenic shock and HF [17,18]. Dobutamine primarily stimulates β 1 -adrenergic receptors, and partly the β 2 -adrenergic receptors, in the heart to produce dose-dependent ionotropic and chronotropic effects, and is used for maintenance of cardiac functions in severe heart failure [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Both dobutamine and rhBNP are used for the treatment of severe and acute decompensated HF, which is the most common cause of in-hospital mortality and readmissions among elderly patients [27,15]. However, the negative effects of dobutamine, such as increased cardiac output and elevated myocardial oxygen demand, increase the risk of myocardial ischaemia, tachyarrhythmias and ventricular dysfunction in HF patients [17,13]. Similarly, the side effects of rhBNP treatment in HF patients include low blood pressure, headache, nausea, decreased heart rate and impaired renal function [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…13,74 A vasoconstrictor strategy for CS treatment promotes an approach based on BP, which, while important, does not necessarily reflect CO or tissue perfusion. 64,75 The important interpatient variability may preclude application of a rigid oversimplified therapeutic scheme. Vasopressors can be employed as an emergency treatment, but this can rapidly be modified on the basis of a personalized therapeutic strategy.…”
Section: Maximum Vasoconstrictionmentioning
confidence: 99%